AN EXPLORATION OF ANTIMULTIGROUP EXTENSIONS - Peter, Chinedu; Balogun, Funmilola; Adeyemi, Omotosho Adewumi (FUDMA JOURNAL OF SCIENCES, 2024)
This research paper pioneers an innovative extensions of antimultigroup theory by seemingly integrating the concept of cuts and comultiset, thereby revolutionizing the field. Notably, we demonstrate that the root sets of antimultigroup sums and differences are subgroups, uncovering a profound connection. Furthermore, we establish that if  is a complete sub-antimultigroup of  such that all the counts in  are factors of their corresponding counts in .  Finally, we prove that the cuts of antimultigroup unions and intersections also form subgroups, further enriching our understanding of these complex structures.
Keywords: Multiset; Multigroup; Group; Antimultigroup